Systematic Evaluation of the Emergency Accommodation Potential of Existing Public Buildings - Idemen, Ayşe Esra; Şener, Sinan Mert (IGI Global, 2022)
Adaptive reuse (AR) —the process of adapting existing buildings for new purposes can be an effective post-disaster strategy to shelter displaced people in densely built environments. As the literature documents no systematic tools to measure the suitability of existing buildings as collective shelters, this paper presents a multi-criteria shelter assessment tool (CS/ARP) for pre-disaster and rapid post-disaster uses. The study aims to discuss the CS/ARP methods’ potentials and provide evidence-based arguments for proactive disaster preparedness along with possible BIM and GIS connections. The proposed tool was tested through an in-depth case study involving the assessments of 3 school buildings in Istanbul. The assessments containing 119 categorized criteria under scorable assessment forms, facilitate the selection of the best building options among alternatives in a predetermined urban area. Decision-makers, designers and researchers may benefit from the proposed assessment approach with a specific focus on the temporary use of existing buildings with high digitalization potential.